Reports of my death are premature : a biography of the public intellectual - Fordham, Helen A. (Curtin University, 2011)
This thesis examines the function, role and nature of the public intellectual in contemporary society to establish the ethical grounds upon which they can justify political intervention. It begins by arguing that the public intellectual, contrary to reports during the 1980s, is not dead: its transformation from Immanuel Kant’s “legislator” to Zygmunt Bauman’s “interpreter” signals, not a decline, but rather a historically contingent function that adapts to ideological and structural shifts in the public domain. Despite these adaptations, however, the public intellectual remains identifiable across the histories of western societies by a consistency of underlying critical, political and ethical functions. These functions were first outlined by Kant as mechanisms to regulate civil society, and they remain evident in the Australian History Wars of the 1990s and the David Hicks case during the first decade of the twenty-first century.Nonetheless, contemporary public intellectuals face a fundamental dilemma: the absence of universal “truths” by which to establish ethical grounds for any assertion of values that sustain democratic civil society and justify political intervention in it. The thesis proposes that one way to think about this challenge is to consider the critical/self-fashioning ethics of Michel Foucault and the critical humanism of Edward Said. These theories affirm a public intellectual who continues to work against the practices that restrict freedom. Together they argue that social values and concepts are made by history and can therefore be renegotiated, and that political engagement is made possible by an ethical commitment to the critically conscious citizen as the site of social renewal.